Heavier Lies Her Crown: Gendered Patterns of Leader Emotional Labor and Their Downstream Effects - Vial, Andrea C.; Cowgill, Colleen M. (Frontiers in Psychology, 2022)
Women use power in more prosocial ways than men, and they also engage in more emotional labor (i.e., self-regulate their emotions to respond and attend to the needs and emotions of other people in a way that advances organizational goals). However, these two constructs have not been previously connected. We propose that gendered emotional labor practices and pressures result in gender differences in the prosocial use of power. We integrate the literature on emotional labor with research on the psychology of power to articulate three routes through which this happens. First, women may be more adept than men at the intrapersonal and interpersonal processes entailed in emotional labor practices—a skill that they can apply at all hierarchical levels. Second, given women’s stronger internal motivation to perform emotional labor, they construe power in a more interdependent manner than men, which promotes a more prosocial use of power. As a result, female powerholders tend to behave in more prosocial ways. Third, when they have power, women encounter stronger external motivation to engage in emotional labor, which effectively constrains powerful women’s behaviors in a way that fosters a more prosocial use of power. We discuss how, by promoting prosocial behavior among powerholders, emotional labor can be beneficial for subordinates and organizations (e.g., increase employee well-being and organizational trust), while simultaneously creating costs for individual powerholders, which may reduce women’s likelihood of actually attaining and retaining power by (a) making high-power roles less appealing, (b) guiding women toward less prestigious and (c) more precarious leadership roles, (d) draining powerful women’s time and resources without equitable rewards, and (e) making it difficult for women to legitimize their power in the eyes of subordinates (especially men). Thus, emotional labor practices can help explain the underrepresentation of women in top leadership positions.